Exploring sports coaches` experiences of using a contemporary pedagogical approach to coaching: an international perspective - Stone, J. A.; Rothwell, M.; Shuttleworth, R.; Davids, K. (Qualitative Research in Sport, Exercise and Health, 2021)
Nonlinear contemporary coaching approaches are becoming more prominent in academic research, although there is still limited take-up by sports practitioners. Research has investigated why coaches continue to use traditional reproductive pedagogical approaches. However, there is limited understanding of insights and experiences of sports coaches who have switched to contemporary approaches in practice. This study aimed to: (i) explore insights of coaches who are adopting contemporary approaches to understand why they eschewed more traditional approaches and (ii) gain information on their experiences when implementing these contemporary approaches into their practice. To address these aims, 15 experienced professional individual and team sports coaches from a range of countries (i.e. Australia, Netherlands, Portugal, Sweden, UK, USA), were interviewed. Thematic analysis revealed 59 lower-order themes and 10 higher-order themes, organised into 3 dimensions; (i) factors underpinning the coaches` approach to athlete learning; (ii) learning approaches; and (iii), responses to contemporary pedagogical approaches. Coaches reported a typical culture of traditional methods of learning within their sports, which they believed were not effective in developing athlete performance. Hence, they elected to adopt a contemporary non-linear, individualised, adaptive approach, emphasising representative learning designs. Results suggested that typical reactions to this approach included resistance from stakeholders. However, coaches continued to use this approach and expressed the importance of effective communication with stakeholders to enable acceptance of the contemporary approaches of learning. Findings suggest how continued integration between experiential and empirical knowledge of practitioners may increase the acceptance of contemporary pedagogical approaches, facilitating acceptance of new approaches to learning.